Tantalum oxynitride thin films: mechanical properties and wear behavior dependence on growth conditions - Cristea, D. (2014)
Tantalum oxynitride (TaNxOy) thin films were produced by magnetron sputtering. This work analyzes and compares the mechanical properties and the wear behavior of the films, taking into account the differences promoted by changes in composition and structure, caused by the variation of the partial pressure of the reactive gases (P(N2+O2)) and by the polarization of the substrate holder. Besides the change in composition, the variation of P(N2+O2) causes significant changes in the morphology and structure of the films. Those produced with low P(N2+O2) evidence a higher crystallinity and, in these conditions, the films exhibit hardness around 20 GPa. Films producedwith higher P(N2+O2) exhibit higherO content, are amorphous and the hardness is significantly lower. The substrate bias does not influence the adhesion of the films to the high speed steel substrate, but influences the mechanical properties, particularly the hardness, at low P(N2+O2) regime. Films with higher crystallinity exhibit higher hardness, but in the low P(N2 + O2) regime, those who were produced with polarization are harder. Although some dependence may be established for set B films, the hardness is not as influent on the wear resistance of the TaNxOy films as the friction coefficient.